The Current Situation and Countermeasures of Quality Education in China in the Context of Marxism - Chen, Shiming (International Journal of Social Sciences and Public Administration, 2024)
The purpose of quality education is to improve the quality of human beings in all aspects and to promote the comprehensive development of human beings. However, according to the current view, there are still many problems in the concept of quality education and the implementation of quality education, so far it has not been able to overcome the cage of exam-oriented education, which hinders the implementation of quality education. In the era of value pluralism, quality education puts higher and higher demands on us. Utilizing the classical philosophical theories of Marxism is of vital importance in guiding the development of quality education in contemporary China.